2019
DOI: 10.1038/s41598-019-42548-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of nasal microbiota and its interaction with surface microbiota among residents in healthcare institutes

Abstract: Nasal microbial communities may have crucial implications for human health, including for residents of healthcare institutes (HCIs). Factors that determine the diversity of nasal microbiota in HCIs remain unclear. Herein, we used 16S rRNA amplicon sequencing to investigate the relationship between nasal and surface microbiota in three HCIs. Participants were classified into a hospitalised or nonhospitalised group based on their most recent date of hospitalisation. A total of 88 nasal samples and 83 surface sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 47 publications
5
39
0
Order By: Relevance
“…Interestingly, reduced diversity in the bNM was identi ed also in other respiratory diseases such as in patients with Chronic Rhinosinusitis (CRS) [56,57], in patients with asthma [58], and in patients affected by granulomatosis with polyangiitis [59]. The importance of a diverse microbiota has been widely documented as pivotal in maintaining the mucosa integrity and an effective immune system [16,45,60]. Moreover, the di culty in de ning clusters between AR patients and HS group, when the disease status was considered, could be attributed to the greater intra-group distances found in the AR patients compared to the ones observed in the HS group.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, reduced diversity in the bNM was identi ed also in other respiratory diseases such as in patients with Chronic Rhinosinusitis (CRS) [56,57], in patients with asthma [58], and in patients affected by granulomatosis with polyangiitis [59]. The importance of a diverse microbiota has been widely documented as pivotal in maintaining the mucosa integrity and an effective immune system [16,45,60]. Moreover, the di culty in de ning clusters between AR patients and HS group, when the disease status was considered, could be attributed to the greater intra-group distances found in the AR patients compared to the ones observed in the HS group.…”
Section: Discussionmentioning
confidence: 99%
“…Insights into the shape of the adult nasal microbiome can be generated by analysis of residents living in different healthcare institutes, as different environmental factors might influence the composition (i.e., cleaning processes, disinfection of indoor air, or the source of ventilated air). A study from Taiwan found that the nasal microbiome more strongly relates to the environmental surface microbiome, and this was the case when participants from three healthcare institutes were analyzed [35] . A particular influence of the surface microbiome was observed in participants who have been hospitalized in the year prior to study enrollment, with a significantly higher proportion of microbes derived from surfaces.…”
Section: The (Healthy) Nasal Microbiome and Influences On Diversitymentioning
confidence: 99%
“…In the indoor environment, studies have also drawn the link between microbial composition and endotoxin levels in dust and immuno-protection (e.g., against asthma) (Gehring et al 2008;Stein et al 2016). Other indoor-based studies show airborne microbes contribute to nasal, oral, and skin microbiomes (Lai et al 2017;Chen et al 2019). Studies have also shown that up to 10 6 microbial cells can be found in a cubic meter of air (Šantl-Temkiv et al 2018;Tignat-Perrier et al 2019).…”
Section: Introductionmentioning
confidence: 99%